Intrauterine fetal death: A hospital based cross sectional study - Nath Dhamala, Jiba; Deo, Amit; Kumar Yadav, Siddhartha; Dhakal, Sanam; Neupane, Sulochana; K.C Parajuli, Heera (Birat Journal of Health Sciences, 2024)
Introduction: Intrauterine fetal death (IUFD) is not only a medical concern but also a deeply emotional and societal one which affects the intrinsic human desire for healthy and thriving offspring. Therefore, it is important to meticulously identify the potential causal factors contributing to fetal deaths, which will help to ascertain the likelihood of its recurrence, and subsequently, to strategize for prevention or necessary interventions. Objectives: The objective of the study is to describe the socio-epidemiological and etiological characteristics ofIUFD. Methodology: This descriptive cross-sectional study was conducted in the Department of Obstetrics and Gynaecology, Birat Medical College and Teaching Hospital, Biratnagar for a duration of 16 months from May 11st, 2022 to August 31st, 2023. All pregnant women who had IUFD with gestational age of 22 weeks and above were included in the study. Results: During the study period there were total of 5,404 deliveries and among them 73 deliveries were IUFD (13.5 per 1000 live birth). The majority of IUFD, specifically 37 cases (50.4%), were attributed to unexplained etiology. The most common coexisting condition was hypertensive disorder of pregnancy contributing 20.5% followed by Intra-Uterine Growth Retardation (IUGR) in 11(15.1%) cases. Conclusion: There is a significant burden of stillbirths, which will have effect in physical and psychological well-being along with socio-economic impact for grieving parents. Though hypertensive disorder, IUGR and diabetes were the major identified co-morbidities, more than half of the stillbirths were unexplained. This warrants the need of consistent antenatal care (ANC) visits and timely hospital admission for its aversion.